1988
DOI: 10.1172/jci113707
|View full text |Cite
|
Sign up to set email alerts
|

Oxypurine cycle in human erythrocytes regulated by pH, inorganic phosphate, and oxygen.

Abstract: The effect of pH, P02, and inorganic phosphate on the uptake and metabolism of hypoxanthine by erythrocytes has been studied. Uptake of hypoxanthine and accumulation of inosine 5'-monophosphate (IMP) were markedly increased at acid pH, high external phosphate concentrations, and low Po2. Release of accumulated IMP as hypoxanthine occurred at alkaline pH values and low external phosphate concentrations. Conditions favoring IMP accumulation gave rise, in the absence of hypoxanthine, to a corresponding increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
(17 reference statements)
2
31
0
Order By: Relevance
“…The data for the basal evaluation suggested that the energetic homeostasis was maintained in the RBCs under the present method. The present alkaline information agreed with the changes in the RBCs in alkaline media except the IMP, uric acid and AEC values (Minakami and Yoshikawa 1966;Tsuda et al 1975;Bontemps et al 1986;Berman et al 1988). The IMP value in alkaline samples differed from previous reports because the alkaline evaluations did not observed changes or showed a reduction of IMP.…”
Section: Discussionsupporting
confidence: 85%
“…The data for the basal evaluation suggested that the energetic homeostasis was maintained in the RBCs under the present method. The present alkaline information agreed with the changes in the RBCs in alkaline media except the IMP, uric acid and AEC values (Minakami and Yoshikawa 1966;Tsuda et al 1975;Bontemps et al 1986;Berman et al 1988). The IMP value in alkaline samples differed from previous reports because the alkaline evaluations did not observed changes or showed a reduction of IMP.…”
Section: Discussionsupporting
confidence: 85%
“…The remainder must be supplied from outside, and in our in vitro system at least, from adjacent noninfected red cells. Purine is released from red cells almost exclusively in the form ofhypoxanthine (23,24), and is thus susceptible to oxidation by xanthine oxidase present in the medium. Failure of 1 x 10-7 M chloroquine to abolish parasite growth is indicative of chloroquine resistance (31).…”
Section: Resultsmentioning
confidence: 99%
“…ever, how the purine needs of the replicating parasite can be supplied by hypoxanthine derived from the host cell, since many studies, including our own, have shown that hypoxanthine release from human red cells under physiologic conditions is too slow to match the rate of parasite nucleic acid synthesis (22)(23)(24). During the course of a previous study on the regulation of hypoxanthine turnover in human erythrocytes, we noted that incubation in xanthine oxidase markedly accelerated the rate of ATP catabolism and hypoxanthine release (22).…”
mentioning
confidence: 99%
“…The dashed arrow represents a pathway with no gene yet identified. This figure was modified from reference 39. 0.6 Ϯ 0.2 M) (24), is the primary product of purine catabolism within red blood cells (5,8), is transported across the red blood cell membrane (31), and is effluxed to the outer surface of red blood cells (6). A common phenotype of relapsing fever spirochetes is their adherence to red blood cells during infection in humans and mice (11,15,23).…”
Section: Discussionmentioning
confidence: 99%